A Reader on Classical Islam - Peters, F. E. (Princeton : Princeton University Press, 2001)
To enable the reader to shape, or perhaps reshape, an understanding of the Islamic tradition, F.E. Peters skillfully combines extensive passages from Islamic texts with a fascinating commentary of his own. In so doing, he presents a substantial body of literary evidence that will enable the reader to grasp the bases of Muslim faith and, more, to get some sense of the breadth and depth of Islamic religious culture as a whole. The voices recorded here are those of Muslims engaged in discourse with their God and with each other--historians, lawyers, mystics, and theologians, from the earliest Co.
Book Cover; Title; Copyright; Contents.
Description based on print version record.
Keywords: Islam; Religion; Islam; RELIGION / Islam / General; Electronic books